2006
DOI: 10.1109/tpwrs.2005.861996
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Generation Control in Wind Parks When Carrying Out System Operator Requests

Abstract: This paper proposes an optimized dispatch control strategy for active and reactive powers delivered by a doubly fed induction generator in a wind park. In this control approach, wind turbines are supposed to operate over a deloaded maximum power extraction curve and will respond to a supervisory wind farm control after a request from a system operator for adjusting the outputs of the wind park. The definition of the active and reactive powers operating points, for each wind turbine, is defined from an optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
174
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(174 citation statements)
references
References 9 publications
0
174
0
Order By: Relevance
“…The pitch control and control of the static converters are used to adjust the rotor speed to its optimum value for the required optimum power operation. The measurement wind speed is inaccurate and reliable due to the influences of the rotor effects in the real value of the wind speed [68]. The authors suggested using a combination of rotor speed control and pitch angle control in the low rated rotor speed region simultaneously [69].…”
Section: De-loading Techniques Usedmentioning
confidence: 99%
“…The pitch control and control of the static converters are used to adjust the rotor speed to its optimum value for the required optimum power operation. The measurement wind speed is inaccurate and reliable due to the influences of the rotor effects in the real value of the wind speed [68]. The authors suggested using a combination of rotor speed control and pitch angle control in the low rated rotor speed region simultaneously [69].…”
Section: De-loading Techniques Usedmentioning
confidence: 99%
“…In variable speed wind turbines (VSWTs), in addition to pitch control, rotor speed control can also be used to run a wind turbine with a reduced load to maintain a reserve capacity [4].…”
Section: B Output Regulation Through Rotor Speed Controlmentioning
confidence: 99%
“…During transient conditions, additional controllers could be installed on the converters or pitch controllers to achieve fast active power controls [21][22][23][24][25][26][27][28]. In some studies, variable-speed wind generators could transiently support system frequency by implementing kinetic energy-based active power control techniques such as "hidden" inertia emulation, fast power reserve emulation, inertia droop control, etc.…”
Section: Fast Active Power Control Of Wind Generatorsmentioning
confidence: 99%